Aerodynamic Performance Enhancement of an Axisymmetric Deflector Applied to Savonius Wind Turbine Using Novel Transient 3D CFD Simulation Techniques - Aboujaoude, Hady; Bogard, Fabien; Beaumont, Fabien; Murer, Sébastien; Polidori, Guillaume (Energies, 2023)
Many recent studies show that the performance of Savonius turbines can be considerably increased by using wind deflectors. Axisymmetric deflectors are particularly interesting; they concentrate the wind flow in all directions. This study aims to aerodynamically optimize the truncated cone deflector shape through transient 3D CFD simulations using sliding mesh techniques. To reduce the mesh size and thus the simulation time, symmetrical boundary conditions were applied to rotating body faces. A mesh grid sensitivity study was conducted to define the optimum mesh size. Additionally, hybrid numerical approaches combining coupled and SIMPLE solvers were particularly influential in reducing computational time. Concave- and convex-arced-shaped faces deflectors were compared to the original truncated cone deflector, showing an increase in the performance for the convex type and a decrease for the concave one. Then, eight cases involving convex spline shape deflectors were simulated. All these deflectors had an equal volume to the original truncated cone deflector. One of the cases showed a 20% average increase in the performance over the original deflector. This result shows the importance of the geometrical shapes in the design of axisymmetric deflectors.
Number: 2
Keywords: URANS; aerodynamics; computational fluid dynamics (CFD); numerical solvers; transient three-dimensional simulations; vertical axis wind turbine; wind deflector